Coordinated synchronization of multiple robot manipulators with dynamical uncertainty - Cicek, E.; Dasdemir, J.; Zergeroglu, E. (SAGE PUBLICATIONS LTD, 2015)
In this paper, the position synchronization problem of robotic manipulators, in master-slave form, under a coordinated control scheme is addressed in both joint and task/operation space. The manipulators are considered fully actuated, with all system states measurable. The desired trajectory is only accessible to the master robot and information flow is only from master to slaves as opposed to the usual but restrictive assumption of cooperative synchronization scheme. Despite the parametric uncertainty in the system dynamics the proposed adaptive controllers yield asymptotic synchronization of the network in both joint and task space. Lyapunov-based arguments are applied in the stability proofs and controller design. Simulation studies performed on a two-robot manipulator network are presented to demonstrate the viability and performance of the proposed control methods.
Keywords: Coordinated control; synchronization; adaptive control; master-slave robot manipulators; parametric uncertainty; TRACKING; Automation & Control Systems; Instruments & Instrumentation